Exploring the Hidden Depths: Speleotourism and Cave Exploration in Boisun District, Uzbekistan: Menjelajahi Kedalaman yang Tersembunyi: Speleotourism dan Penjelajahan Gua di Distrik Boisun, Uzbekistan - Eshniyoz , Ziyodullayeva Ogilshod (Universitas Muhammadiyah Sidoarjo, 2023)
This scientific article presents an overview of speleotourism and cave exploration opportunities in Boisun District, Uzbekistan. The study aims to highlight the unique natural objects, such as Teshik Stone Cave, Boy Bulak Cave, Dark Star Cave, and Khoja Gur Gur Ota, along with their distinctive characteristics. The article discusses the organization of speleological expeditions, cave routes in sports tourism, and the equipment required for cave exploration. The methods employed include cave surveys, expeditions, and documentation of cave characteristics. The results reveal fascinating details about the caves, including their geological features, underwater lakes, intricate passages, and historical significance. Implications of these findings emphasize the potential for further research, conservation efforts, and the development of sustainable speleotourism in Boisun District, offering unique opportunities for adventure seekers and scientists alike.Highlights: Speleotourism in Boisun District: Explore the thrilling world of caves and engage in speleotourism activities in the captivating Boisun District of Uzbekistan. Unique Natural Objects: Discover the fascinating natural objects of Boisun District, including Teshik Stone Cave, Boy Bulak Cave, Dark Star Cave, and Khoja Gur Gur Ota, each offering distinct geological features and historical significance. Opportunities for Adventure and Research: Embark on speleological expeditions, uncover hidden depths, and contribute to the exploration and documentation of these caves, presenting opportunities for adventure enthusiasts and scientific researchers. Keywords: Speleotourism, Cave exploration, Boisun District, Uzbekistan, Natural objects